Thrombotic microangiopathy by COVID-19 superposed to non-dialytic chronic kidney disease: case report (Research, Society and Development, 2023)
Objective: To describe a case of thrombotic microangiopathy due to COVID-19 superimposed on non-dialytic CKD, who was under medical care by the Nephrology ward team at a referral center in northeastern Brazil. Method: A case report study in which we present a case of TMA with severe kidney damage triggered by SARS-CoV-2 in a patient with previous chronic nephropathy, who evolved with the need for hemodialysis. Results: TAM associated with SARS-CoV-2 seems to be related to the uncontrolled activation of an alternative complement pathway and the alteration of the integrity of the vascular endothelium, leading to the release of inflammatory cytokines and consequent activation of the local coagulation cascade. To improve the outcome of these patients, it is necessary to quickly identify the TMA, offer supportive therapy and, when applicable, specific treatment according to the underlying pathophysiology. Discussion: COVID-19 can manifest as multiorgan dysfunction, with pulmonary involvement being the most common. Exaggerated immune response in the form of unrestricted complement activation and cytokine storm may be a key factor for widespread organ damage. There may be hypercoagulability and a high rate of thrombosis. Although macrovascular thrombosis is common in these individuals, the frequent finding of microvascular thromboses raises the possibility of thrombotic microangiopathy (TAM) as a contributing factor to multiorgan complications, including the kidney. Conclusion: The management of TMA is a challenge and survival rates are directly related to the implementation time of adequate treatment.